Transcriptome, enzyme activity and histopathology analysis reveal the effects of high level of dietary carbohydrate on glycometabolism in juvenile golden pompano, Trachinotus ovatus. (15th May 2019) - Liu, Kang; Tan, Beiping; Zhang, Wei; Liu, Hongyu; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang; Zhang, Haitao
Abstract: Golden pompano ( Trachinotus ovatus ) is an important aquaculture species in China and broadly cultivated in Asia–Pacific region. Our previous study found that T. ovatus had a better tolerance to the high level of carbohydrate in diet (360 g/kg) compared to Micropterus salmoides . Present study investigated the tolerance mechanism of T. ovatus to high level of dietary carbohydrate (PH‐360 g/kg of corn starch) on transcriptome level using Illumina sequencing compared to optimum level of dietary carbohydrate (PM‐240 g/kg corn starch). A total of 208, 952, 492 reads were obtained and assembled into 62, 377 unigenes with an average length of 822 bp and a range of 200–16, 206 bp. Transcriptome annotation revealed that 27, 636 unigenes with a cut‐off e‐value of 10 −5 were functionally annotated. Specifically, 7, 903 unigenes were clustered into 24 functional categories by searching against the COG database, 12, 161 unigenes to 84 GO terms, 26, 835 unigenes to Nr database and 23, 681 unigenes to SWISS‐PROT database. In addition, 13, 739 unigenes were grouped into 240 KEGG pathways. There are 3, 461 differentially expressed genes in PH compared to PM, in which 3, 059 unigenes were significantly upregulated and 402 unigenes were significantly downregulated. Twelve key genes related to carbohydrate metabolism were further validated by quantitative real‐time RT–PCR, and the results were consistent with those of transcriptome profile.Under high level of dietary carbohydrate (PH‐360 g/kg), the results indicate that T. ovatus can adapt to the high level of dietary carbohydrate by enhancing glycolysis with the increased heaptic HK enzyme activity ( p > 0.05), reducing gluconeogenesis with the decreased trend of PEPCK enzyme activity and maintaining the homeostasis of carbohydrate metabolism‐related hormones and hormone receptor gene expressions. Histopathological examination has shown that liver cavity area was significantly increased ( p > 0.05), but no visible nutritional diseases are found in fish. This study provides a valuable understanding of the molecular responses of T. ovatus fed by the high level of dietary carbohydrate (PH‐360 g/kg).